2008
DOI: 10.1111/j.1610-0387.2008.06751.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of itraconazole for treatment of fungal infections of skin, nails and mucous membranes

Abstract: Itraconazole is an antifungal drug from the triazole group with distinct in vitro activity against dermatophytes, yeasts and some molds. Itraconazole has a primarily fungistatic activity. Itraconazole accumulates in the stratum corneum and in nail material due to its high affinity to keratin, as well as in sebum and vaginal mucosa. Together with terbinafine and fluconazole, itraconazole belongs to the modern highly effective systemic antifungal drugs with a favorable risk-benefit ratio and for this reason is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 56 publications
1
19
0
4
Order By: Relevance
“…Tetracyclines, including doxycycline, have previously been associated with modulation of secretory phospholipases ( 84,85 ) as well as the inhibition of metalloproteinases, downregulation of cytokines, and cell proliferation ( 86 ), all of which should be considered in regard to the phenotypic characterization of the Barth syndrome mouse model. Because the inducible Taz KD mice were compared with wild-type age-matched littermates also fed a doxycycline-enriched diet, the differential phenotype displayed represents the pathological changes induced by cardiac myocyte tafazzin defi ciency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetracyclines, including doxycycline, have previously been associated with modulation of secretory phospholipases ( 84,85 ) as well as the inhibition of metalloproteinases, downregulation of cytokines, and cell proliferation ( 86 ), all of which should be considered in regard to the phenotypic characterization of the Barth syndrome mouse model. Because the inducible Taz KD mice were compared with wild-type age-matched littermates also fed a doxycycline-enriched diet, the differential phenotype displayed represents the pathological changes induced by cardiac myocyte tafazzin defi ciency.…”
Section: Discussionmentioning
confidence: 99%
“…Because the inducible Taz KD mice were compared with wild-type age-matched littermates also fed a doxycycline-enriched diet, the differential phenotype displayed represents the pathological changes induced by cardiac myocyte tafazzin defi ciency. Furthermore, it was previously reported that the level at which doxycycline or tetracyclines inhibited these biological processes in vitro far exceeds the pharmacological dose that would be administered in vivo ( 86,87 ), thus demonstrating the strength of the pathological fi ndings manifest during tafazzin defi ciency that are reversible upon its reexpression.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC of luliconazole (MIC 90 ) has been found to be 4-to 1,000-fold lower than the MIC 90 s reported for a number of antifungals, including terbinafine, bifonazole, and lanoconazole (12,(14)(15)(16). Luliconazole is also more potent in vitro than terbinafine and bifonazole in inhibiting C. albicans (14).…”
mentioning
confidence: 88%
“…On each of these days, blood was collected immediately prior to dosing and then at 1,3,6,9,12,16,20, and 24 h after dosing. Additional blood draws were conducted prior to dosing on days 3, 4, 5, 11, 18, 22, and 25 and following the cessation of treatment on days 31, 32, 33, and 36 (the last study visit, which occurred 7 days after the last treatment application).…”
Section: Study Drug Luliconazole Is (mentioning
confidence: 99%
“…O itraconazol é efi caz no tratamento de uma grande variedade de micoses superfi ciais, por se acumular nos ceratinócitos e atingir altas concentrações na secreção sebácea e nos pelos (KORTING & SCHÖLLMANN, 2009).…”
unclassified